The Effect of Intravenous Glutamine Administration in Lowering AIF Expression in Renal Tubular Cells - Raihan Akbar Muhammad; Imam Susilo; Eko Budi Koendhori; Bambang Purwanto (Majalah Biomorfologi)
Highlights